A comparative study of behavioural and thermoregulatory responses of blue wildebeest and gemsbok to aridity - Boyers, Melinda Frances (My University, 2018)
Future climate change scenarios predict that many arid and semi-arid ecosystems within southern Africa, will get warmer and drier with increased frequency of droughts. Although the effects of climate change may only be apparent over a few decades, understanding the physiological and behavioural flexibility of individuals currently inhabiting hot and dry climates provides an analogue for conditions likely to become prevalent in the future. To enhance our understanding of how a species may respond to future hotter and drier environments, I set out to investigate seasonal variation in behaviour and thermoregulation of two ungulate species with differing water dependency in a semi-arid savanna. I focused on thermoregulatory (body temperature) and behavioural responses (activity and microclimate selection) of the water-dependent blue wildebeest (Connochaetes taurinus), and the arid-adapted gemsbok (Oryx gazella gazella) free-living in the Kalahari. Both species prioritised behavioural thermoregulation in the form of cool microclimate selection during the heat of the day and reduced both diurnal and 24 h activity, particularly when conditions were hot and dry. Both species experienced high maximum 24 h body temperature when conditions were hot and low minimum 24 h body temperatures when conditions were dry, resulting in a large amplitude of 24 h body temperature rhythm during the hot dry period. Yet, wildebeest appeared to be more sensitive to changes in aridity with a larger amplitude of 24 h body temperature rhythm compared to gemsbok (3.1 ± 0.2 °C vs. 2.1 ± 0.5 °C), during the drought. These seasonal analyses imply that the species behavioural and thermoregulatory responses were influenced by seasonal changes in water and forage availability. Low minimum 24 h body temperatures may result from an energy deficit during the dry season, but no study to date has explicitly linked changes in body temperature of free-living ungulates, to forage quality within the environment. I therefore investigated the influence of vegetation greenness on body temperature and activity of blue wildebeest and gemsbok inhabiting the same environment. I then investigated if the responses of gemsbok were heightened in a more arid environment. I used Normalized Difference Vegetation Index (NDVI) as a standardized index of vegetation greenness, which can be considered a proxy for vegetation productivity and quality. Both species reduced total 24 h activity and became hypothermic when exposed to brown vegetation but when exposed to brown vegetation minimum 24 h body temperatures were lower for blue wildebeest compared to gemsbok. When exposed to more extreme aridity, gemsbok showed an exaggerated lowering of minimum 24 h body temperatures. Under conditions of low food availability, the cost of thermoregulation may become too demanding. Therefore, when food resources are limited in quality, wildebeest and gemsbok in arid regions appear to prioritize the conservation of energy over the maintenance of a high body temperature. Within seasonal environments, access to water is often the limiting factor for plants and animals. I therefore investigated how distance to water (i.e., how frequently animals were likely to have accessed drinking water) during the hot season influenced microclimate selection, activity and body temperature of blue wildebeest and gemsbok. Both species selected similarly cool microclimates during the heat of the day, with slight enhancement in the quality of microclimates selected when they were further from water. Both species decreased activity during the heat of the day when they were further from water. Gemsbok were able to compensate for their reduced activity during the heat of the day and showed little change in total 24 h activity, but wildebeest showed a more exaggerated decline in activity during the heat of the day for which they were unable to compensate, i.e. total 24h activity of wildebeest declines when they were further away from water sources. Both species displayed higher maximum 24 h body temperatures when they were further away from water, with the hyperthermia being exaggerated for the wildebeest compared to gemsbok. Hyperthermia in both species resolved following the first rains and likely access to drinking water. Access to water appears to be the primary driver towards hyperthermia in the wildebeest, potentially resulting from dehydration during thermal stress. In summary, I have investigated behavioural and thermoregulatory flexibility that large African ungulates currently inhabiting hot and dry climates currently employ. I have shown that ungulates in the Kalahari may differ in their use of microclimate selection and activity patterns to buffer thermal, energetic and water stressors. My study is unique in that I have looked at where the animal was in space and time and linked it to their physiological and behavioural responses. I have, therefore, quantified microclimate selection, activity and body temperature responses in relation to NDVI and distance to water and have shown that the driving mechanisms behind the seasonal changes of body temperature and activity patterns is access to energy and water. I have further enhanced our existing knowledge and created the link between body temperature, vegetation quality and distance to surface water for antelope of the Kalahari and effectively assessed a functional trait. With climate change predicted to increase ambient temperatures and have less predictable rainfall in the semi-arid Kalahari, wildebeest will be forced to remain within the Kalahari, because historical migratory paths have been blocked by fences, and they may not have the behavioural and physiological flexibility to survive a hotter and drier future.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2018.
Keywords: Arid regions ecology; Land use; Microclimatology